FUNCTION AND DUTIES OF TRADITIONAL INSTITUTIONS IN IMPLEMENTING VILLAGE GOVERNMENT IN LUWU UTARA REGENCY - ANDI WINDA SARI; AMINUDDIN ILMAR; A. SURIYAMAN MUSTARI PIDE (Awang Long Law Review, 2021)
In essence, customary institutions are partners of the village government. This is where the understanding and capability of traditional leaders and officials in a customary institution are needed in carrying out their roles. So that then the existing village government can better understand that the village government itself is carried out with respect and/or based on community initiatives, the rights of origin and traditional rights of the village. This paper analyzes the implementation of the functions and duties of customary institutions in the administration of the Hono Village government. The research method used in the empirical research, namely by examining the implementation of the functions and duties of customary institutions in the implementation of Village Government in Hono Village, Seko District, Luwu Utara Regency and the obstacles to implementing the functions and duties of Traditional Institutions in implementing Village governance in Hono Village, Seko District, Luwu Utara Regency. The types of data used are primary data and secondary data obtained from interviews and documentation. All data collected were analyzed qualitatively. The results showed that the implementation of Village Goverment in Hono Village, Seko District, Luwu Utara Regency has been implemented effectively and efficiently. This is shown by the harmonious cooperation between the traditional Hono village government, Hono traditional institutions and other village officials in developing consensus deliberations for decision making in village deliberations as well as the development of customary values in resolving land disputes and conflicts in the social life arrangements of the indigenous Hono community. In addition, the hono customary institution has also carried out functions in protecting the cultural identity and traditional rights of indigenous peoples including marriage and other kinship elements. On the basis of this, it can be concluded that the hono village customary institution has carried out its functions and duties as stipulated in the Minister of Home Affairs Regulation Number 18 Year 2018 concerning Village Community Institutions and Village Traditional Institutions.